The effectiveness of Praise and Worship Services in increasing Congregational Faith in Churches - Yoel Betakore; Fredik Melkias Boiliu; Jowel Elia Zakaria; Daniel Pribadi (Pharos Journal of Theology, 2023)
Praise and worship service plays a very important role in the worship system of some Christian denominations. Generally, praise and worship is an expression of the heart overflowing with gratitude to glorify God's name revealed through music. This study aims to determine the effectiveness of praise and worship service in increasing the congregations faith in the Indonesian Bethel Church River of Life Pamulang, South Tangerang Indonesia. The research method used in this research work is a descriptive qualitative one. Qualitative research aims to uncover symptoms in a holistic-contextual manner where data collection takes place naturally and researchers serve as the key instruments. To obtain information related to the effectiveness of understanding praise and worship service in increasing the congregation faith in the church, researchers conducted a literature study, and held interviews with a church pastor and some of the congregation. The results showed that there has been an application of praise and worship services carried out by the congregation so that it has experienced faith growth, but it needs to be further enhanced so that it is more effective and sustainable.